Relational contracts and inequity aversion - Jenny Kragl; Julia Schmid (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
We study the effects of envy on the feasibility of relational contracts in a standard moral hazard setup with two agents. Performance is evaluated via an observable, but non-contractible signal which reflects the agent's individual contribution to firm value. Both agents exhibit disadvantageous inequity aversion. In contrast to the literature, we find that inequity aversion may be beneficial: In the presence of envy, for a certain range of interest rates relational contracts may be more profitable. Furthermore, for some interest rates reputational equilibria exist only with inequity averse agents.
Keywords: D63; D82; M52; M54; 330; principal-agent; relational contract; inequity aversion; envy